Smart building systems for architects, owners, and builders - Sinopoli, Jim (Elsevier/Butterworth-Heinemann, 2010)
Smart Buildings Systems for Architects, Owners and Builders is a practical guide and resource for architects, builders, engineers, facility managers, developers, contractors, and design consultants. The book covers the costs and benefits of smart buildings, and the basic design foundations, technology systems, and management systems encompassed within a smart building. Unlike other resources, Smart Buildings is organized to provide an overview of each of the technology systems in a building, and to indicate where each of these systems is in their migration to and utilization of the standard un.
Includes index.
Keywords: Intelligent buildings.; Smart materials in architecture.; elektronické knihy; electronic books